2023
DOI: 10.1177/10704965231211591
|View full text |Cite
|
Sign up to set email alerts
|

The Emergence of Green Banking: A Sustainable Financing Strategy for Protecting Against Deforestation in ASEAN

Sapto Hermawan,
Zenia Aziz Khoirunisa

Abstract: ASEAN countries face significant environmental challenges contributing to climate change, biodiversity loss, deforestation, and soil degradation. Green banking can help redirect investments toward environmentally friendly activities and discourage deforestation by incentivizing sustainable financing and penalizing unsustainable practices. The article examines the potential benefits of green banking in promoting sustainable financing and discusses the challenges and opportunities for its implementation in ASEAN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Though the performance of banks is assessed in terms of market value, growth, number of customers, customer satisfaction, efficiency and productivity (Bikker & Bos, 2008), green banking performance includes environmental and social performance (Selvam et al, 2016). One of the recent studies has reported that green banking helps redirect investments towards environment-friendly activities by organisations, which reduces soil degradation, deforestation and biodiversity loss (Hermawan & Khoirunisa, 2023).…”
Section: Banking Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Though the performance of banks is assessed in terms of market value, growth, number of customers, customer satisfaction, efficiency and productivity (Bikker & Bos, 2008), green banking performance includes environmental and social performance (Selvam et al, 2016). One of the recent studies has reported that green banking helps redirect investments towards environment-friendly activities by organisations, which reduces soil degradation, deforestation and biodiversity loss (Hermawan & Khoirunisa, 2023).…”
Section: Banking Performancementioning
confidence: 99%
“…Growing environmental concern has resulted in a radical change in the way banks conduct business (Ahuja, 2015;Bowman, 2010). Furthermore, attention has been directed towards environmentfriendly banking practices (Hermawan & Khoirunisa, 2023;Meena, 2013;Shakil et al, 2014). Green banking evolved in the last decade to address banks' negative influence on the environment (Rehman et al, 2021).…”
Section: Introductionmentioning
confidence: 99%